Elevated N6-Methyladenosine RNA Levels in Peripheral Blood Immune Cells: A Novel Predictive Biomarker and Therapeutic Target for Colorectal Cancer - Xie, Jinye; Huang, Zhijian; Jiang, Ping; Wu, Runan; Jiang, Hongbo; Luo, Chuanghua; Hong, Honghai; Yin, Haofan (Frontiers in Immunology, 2021)
Effective biomarkers for the diagnosis of colorectal cancer (CRC) are essential for improving prognosis. Imbalance in regulation of N6-methyladenosine (m6A) RNA has been associated with a variety of cancers. However, whether the m6A RNA levels of peripheral blood can serve as a diagnostic biomarker for CRC is still unclear. In this research, we found the m6A RNA levels of peripheral blood immune cells were apparently elevated in the CRC group compared with those in the normal controls (NCs) group. Furthermore, the m6A levels arose as CRC progressed and metastasized, while these levels decreased after treatment. The area under the curve (AUC) of the m6A levels was 0.946, which was significantly higher than the AUCs for carcinoembryonic antigen (CEA; 0.817), carbohydrate antigen 125 (CA125; 0.732), and carbohydrate antigen 19-9 (CA19-9; 0.771). Moreover, the combination of CEA, CA125, and CA19-9 with m6A levels improved the AUC to 0.977. Bioinformatics and qRT-PCR analysis further confirmed that the expression of m6A modifying regulator IGF2BP2 was markedly elevated in peripheral blood of CRC patients. Gene set variation analysis (GSVA) implied that monocyte was the most abundant m6A-modified immune cell type in CRC patients’ peripheral blood. Additionally, m6A modifications were negatively related to the immune response of monocytes. In conclusion, our results revealed that m6A RNA of peripheral blood immune cells was a prospective non-invasive diagnostic biomarker for CRC patients and might provide a valuable therapeutic target.